What Makes Hosts Trust Airbnb? Antecedents of Hosts' Trust toward Airbnb and Its Impact on Continuance Intention. (April 2020) - Wang, Yichuan; Asaad, Yousra; Filieri, Raffaele
Sharing economy platforms are growing at an unprecedented rate. Travel and tourism scholars have been focusing on customers' sharing intention, yet the literature has largely overlooked what makes sharing service providers trust a sharing economy platform and decide to continue using it. Drawing on sociotechnical theory and the information systems success model, in conjunction with privacy concerns and economic value perspectives, this study develops an integrated model of antecedents and consequences of trust toward sharing economy platforms. Data from 606 Airbnb hosts were analyzed through structural equation modeling. Our research documents the importance of social antecedents (i.e., social value orientation and social utility), technical antecedents (i.e., system quality, service quality, and information quality), economic antecedents (i.e., monetary rewards) and privacy assurance antecedents (i.e., perceived effectiveness of privacy policy) in shaping hosts' trust toward Airbnb, thereby enhancing their continuance intention with regard to using the platform.